2023
DOI: 10.1111/eea.13295
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive metabolites from autochthonous lactic acid bacteria inhibit the growth of Melissococcus plutonius, causal agent of European foulbrood disease in honey bees

Abstract: European foulbrood (EFB), a disease affecting larvae of honey bees, Apis mellifera L. (Hymenoptera: Apidae), is caused by the Gram-positive bacterium Melissococcus plutonius corrig. (ex White) Bailey & Collins (Vasquez et al., 2012). Other secondary invaders like Paenibacillus alvei (Cheshire & Cheyne) Ash et al., Brevibacillus laterosporus (Laubach) Shida, and Enterococcus faecalis (Andrewes & Horder) Schleifer & Kilpper-Bälz are also associated with EFB (Pietropaoli et al., 2022). This bacterial disease is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although the 48 h culture supernatant showed inhibitory effects on both Gram-positive and Gram-negative pathogens, P. aeruginosa was the most resistant. Other authors [ 103 ] reported that LAB strain metabolites, including L. plantarum , L. acidophilus , L. rhamnosus , L. apis , and P. acidilactici , were tested against M. plutonius , and the results showed high inhibition of the pathogen. Moreover, the mixture of the four most potent isolates within 96 h reduced M. plutonius survival to 0%.…”
Section: Discussionmentioning
confidence: 99%
“…Although the 48 h culture supernatant showed inhibitory effects on both Gram-positive and Gram-negative pathogens, P. aeruginosa was the most resistant. Other authors [ 103 ] reported that LAB strain metabolites, including L. plantarum , L. acidophilus , L. rhamnosus , L. apis , and P. acidilactici , were tested against M. plutonius , and the results showed high inhibition of the pathogen. Moreover, the mixture of the four most potent isolates within 96 h reduced M. plutonius survival to 0%.…”
Section: Discussionmentioning
confidence: 99%
“…The culture filtrate of this strain demonstrated its capacity to reduce mycotoxins and extend shelf life, using wheat grains as a food model. Moreover, a high concentration of acetic acid inhibits the growth of Melissococcus plutonius and can be used as a biocontrol agent for preventing European Foulbrood disease in honeybees [47]. Overall, organic acids remain a promising option for biopreservation, since they are considered safe for human consumption.…”
Section: Organic Acidsmentioning
confidence: 99%